PRESSURE ULCERS ARE ASSOCIATED WITH SIX-MONTH MORTALITY IN HIP FRACTURE IN ORTHOGERIATRIC CARE - Magny, E. (Innov Aging, 2017)
Pressure ulcers (PU) in hip fracture are associated with poor outcomes. Orthogeriatric management reduces PU incidence in hip fracture in the elderly. However, remaining factors and prognostic associated with PU in hip fracture patients managed in orthogeriatric care pathway are unknown. The objectives were to determine the prognostic of PU in the hip fracture in UPOG, and their associated factor. From June 2009 to April 2015, all consecutive patients, > 70 years old, with hip fracture admitted to an (UPOG) were screened. Patients were included if they were hospitalized for hip fracture and were excluded in presence of pathological fracture or if they were already hospitalized at the time of the fracture. In our unit, orthogeriatric principles are implemented, including a multicomponent intervention to improve PU prevention and management. Patients were followed until 6 months after discharge. 567 patients were included, with an overall 14,4 % 6-month mortality (95% CI: 11.6–17.8%). Of these, 67 patients (12 %) experienced at least one PU. Despite orthogeriatric management, PUs were significantly associated with a low albumin level (RR 0.90, 95% CI:0.84–0.96; p=0.003) and history of atrial fibrillation (RR 1.91, 95% CI:1.05–3.46, p=0.033), coronary artery disease (RR 2.16, 95% CI:1.17–3.99; p=0.014) and diabetes (RR 2.33, 95% CI:1.14–4.75; p=0.02). PU was associated with 6 month mortality (RR 2.38, 95% CI: 1.31–4.32, p=0.044). In elderly patients with hip fracture managed in an orthogeriatric care pathway, PU remained associated with poorly modifiable risk factors and long term mortality.